Stage Monologue and its Linguistic Features (Textual and Prosodic Analysis) - Elena Vasilievna Velikaya (Institut Agama Islam Negeri Palopo, 2022)
Spoken language production is considered to be one of the most difficult aspects of teaching a foreign language. It usually involves mastering pronunciation of sounds and intonation. If nowadays many teachers do not worry about the phonetic details of sounds, there is still focus on intonation as it has a great impact on the comprehensibility of the learner’s English. This is a very important issue for future teachers because correctness of pronunciation is one of the goals of any spoken language programme, with students asked to produce quite extended spoken monologues and to follow the requirements of various intonational styles. The aim of this study is to analyse textual and prosodic characteristics of stage monologue – a text produced on a theatre stage or in a film. Analytical methods were applied in order to obtain information about textual features and prosodic stylistic markers such as pitch level, range, tone modifications, loudness, and tempo, and also to develop style-forming factors in stage monologue. Results show that the stage monologues analysed possess all necessary characteristics of a text: informational content, delimitation, continuum, coherence, cohesion and completeness. Further analysis of stage monologue showed that it can be characterised by such specific features as expressiveness, normativeness, effectiveness, and conversational character. Stage monologues also possess all necessary prosodic markers. Certain style-forming factors of stage monologue were also developed in this study, including delimitation, accentuation of key words, thematic centres and expressively prominent centres, type of composition scheme, and theme. These results will be of significant pedagogical value to students who intend to become English teachers, and to teachers involved in linguistics research.